Analysis on the Interference of Indonesian Morphology in the Translation of Classical Arabic Texts - Syifa Saqmi; Muh. Naim Madjid (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2025)
This study analyzes the phenomenon of morphological interference from Indonesian in the translation of Classical Arabic texts. It examines how Indonesian morphological structures, such as affixation, compounding, and reduplication, affect meaning transfer and grammatical equivalence in Arabic-Indonesian translation. Using a descriptive-analytical approach, the study synthesizes findings from previous research on morphological transfer, interference, and translation strategies in second-language contexts. The results show that learners often unconsciously apply Indonesian morphological patterns during translation, causing mistranslation, redundancy, or distortion of Arabic word forms. These findings indicate that interference arises not only from linguistic differences between Arabic and Indonesian but also from cognitive and cultural factors influencing the translation process. The study concludes that integrating contrastive and contextual approaches in Arabic morphology and translation pedagogy can reduce interference and enhance students’ linguistic awareness and translation accuracy.